Occult lung metastases of papillary thyroid cancer detected in a resected pulmonary arteriovenous malformation specimen. (2022) - Inoue, Tomoyoshi; Oda, Naohiro; Yamada, Eiji; Taki, Takahiro; Mitani, Reo; Takata, Ichiro; Ikeda, Masahiko; Omonishi, Kunihiro; Muro, Masahiko
Abstract: A 41-year-old man with exertional dyspnea was referred to our hospital. Chest computed tomography (CT) showed a pulmonary arteriovenous malformation (PAVM) in the left lingular lobe, and magnetic resonance imaging showed a brain abscess. After antimicrobial therapy, the patient underwent thoracoscopic lingulectomy of the PAVM. Pathological examination revealed lung metastases of papillary thyroid cancer (PTC) that were undetectable by CT. The patient underwent total thyroidectomy and D2b lymphadenectomy for the PTC (the pathological stage was T1bN2M1, Stage II). After surgery, the patient received 100 mCi of 131Iodine; post-treatment scans revealed only neck (remnant) uptake and the patient continued with thyroid hormone replacement therapy. To the best of our knowledge, this is the first report of a case of combined PAVM and occult lung metastases of PTC. Clinicians should remember that they may detect micro lung metastases of any cancer when investigating resected lung specimens. Highlights: Papillary thyroid cancer can cause occult lung metastases undetectable by thin-sliced computed tomography. In this case, occult metastatic papillary thyroid cancer was incidentally discovered in a lung specimen resected during the treatment of a pulmonary arteriovenous malformation. Clinicians should bear in mind the possible detection of micro lung metastases of all cancers when examining resected lung specimens.